Hubungan Beban Kerja dengan Kompetensi Sosial Guru Madrasah Ibtidaiyah Al-Ma'had An-Nur - Riski Eka Purnairawan; Septa Miftakul Janah (Lembaga Sosial Rumah Indonesia, 2022)
The teacher's workload is a work demand that must be done by the teacher professionally and well. On the other hand, teachers must have competent competencies, one of which is social competence. These competencies require teachers to relate harmoniously with students, colleagues at school, and the community where they live. The purpose of this study is to find out how the relationship between the workload received by the teacher and the social competence of a teacher. The research method used is field research with 21 respondents from Madrasah Ibtidaiyah Al-Ma'had An-Nur teachers with an angle distribution technique. The results obtained that the significance value (sig) of the workload variable (X) is 0.748 with a sig value of 0.748 > greater than the probability of 0.05 which means H0 is accepted and H1 is rejected.